Osteogenesis-promoting and anti-infection difunctional porous metal antibacterial coating material based on bimetal ion electroplating and electrolytic pore-forming technology and preparation method of porous metal antibacterial coating material

The porous copper coating materials prepared by applying bimetal ion plating and electrolytic pore-forming technology on bone implantation instruments have been solved, and the problem of poor anti-infection and bone integration effects of traditional bone implantation instruments has been achieved to promote bone repair and anti-bone The dual function of infection.

CN119433639APending Publication Date: 2025-02-14ZHEJIANG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411302009.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Traditional bone implantation devices are not effective in anti-infection and osteointegration, and it is difficult to meet the treatment needs of fractures and bone defect areas at the same time.

Method used

Using a bimetallic ion plating and electrolytic porous bifunctional porous metal antibacterial coating material based on bimetallic ion plating and electrolytic porogenic technology, the copper-magnesium composite coating is formed by forming a copper-magnesium composite coating on the surface of the titanium substrate, and combined with electrolytic deplating and ultrasonic loading technology, Porous copper coated structure, loading the bone-promoting drug.

Benefits of technology

It has achieved the induction of cell adhesion and growth, and coordinated promotion of bone repair, providing a brand new treatment strategy for bone infection prevention and fracture/bone defects, improving the effect of bone integration and anti-infection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119433639A_ABST
    Figure CN119433639A_ABST
Patent Text Reader

Abstract

The invention discloses an osteogenesis-promoting and anti-infection difunctional porous metal antibacterial coating material based on a bimetal ion electroplating and electrolytic pore-forming technology and a preparation method of the porous metal antibacterial coating material. The preparation method comprises the following steps: 1) ultrasonically cleaning a titanium substrate by using an environment-friendly degreasing agent and deionized water to remove impurities and chemical films on the surface of titanium; 2) forming a copper transition layer on the surface of the substrate by using a chemical deposition process; 3) designing a Cu < 2 + > / Mg < 2 + > composite electrolyte formula, and further introducing a copper-magnesium composite coating on the surface of the transition layer in combination with a bimetal ion electroplating process; (4) an alkaline stripping solution is designed for electrolytic stripping of magnesium, and a porous copper coating is obtained; and (5) a sample is soaked in a blood vessel promoting medicine, and after ultrasonic soaking, low-temperature nitrogen drying, dark vacuum packaging and irradiation sterilization are conducted, the required porous copper coating material with the osteogenesis promoting and anti-infection functions is obtained. The coating material can induce cell adhesion and ingrowth at the same time, synergistically promote bone formation, and opens up a brand new strategy for bone repair.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a preparation technology of antibacterial and bone repair materials, and in particular to a bone-promoting and anti-infection dual-function porous metal antibacterial coating material based on dual metal ion electroplating and electrolytic pore-forming technology and a preparation method thereof. Background Art

[0002] Bone defects caused by fractures and trauma are common orthopedic problems in clinical practice, usually caused by traffic accidents, falls, sports injuries or surgical operations. These conditions often require treatment with bone implants or interventional medical devices. Although existing bone implant devices can provide the necessary support and fixation in structure, most of them lack biological activity and are difficult to effectively promote the natural repair and regeneration of bone tissue. At the same time, during the bone healing process, infection at the surgical site can seriously disrupt the fracture healing process and cause serious consequences such as amputation or even death of the patient.

[0003] In response to the poor anti-infection and bone integration effects of traditional bone implant devices, researchers have developed a variety of coating technologies, such as iodine coating and silver coating for antibacterial treatment, and magnesium coating and zinc coating for promoting bone integration. However, these single-function coatings often cannot meet the treatment needs of fractures and bone defects at the same time.

[0004] Based on this, the present invention proposes an osteogenic-anti-infection dual-function porous metal antibacterial coating material based on bimetallic ion electroplating and electrolytic pore-forming technology and its preparation method. The present invention simultaneously introduces a copper-magnesium composite coating on the surface of a titanium substrate by using a bimetallic electrochemical deposition process, and combines electrolytic stripping and ultrasonic loading processes to form a multi-porous copper coating structure that can induce cell adhesion and growth, and loads osteogenic drugs in the pores, providing a new strategy for preventing bone infection and treating fractures / bone defects. Summary of the invention

[0005] The purpose of the present invention is to provide a bifunctional porous metal antibacterial coating material based on dual metal ion electroplating and electrolytic pore-forming technology that promotes bone formation and resists infection, and a preparation method thereof, in order to solve the problems of poor anti-infection and bone integration of traditional bone implant devices. The coating material can also induce cell adhesion and ingrowth, and promote bone formation, thus opening up a new strategy for bone repair.

[0006] The present invention is implemented by the following technical solution, which specifically includes the following steps:

[0007] A method for preparing an osteogenic and anti-infection dual-functional porous metal antibacterial coating material based on dual metal ion electroplating and electrolytic pore-forming technology comprises the following steps:

[0008] 1) Using an environmentally friendly degreasing agent and deionized water under ultrasonic cleaning conditions to remove impurities on the surface of the titanium substrate and perform chemical film removal;

[0009] 2) forming a copper transition layer on the surface of the titanium substrate using a chemical deposition process;

[0010] 3) Design Cu 2+ / Mg 2+ The composite electrolyte formula combines the dual metal ion electroplating process to introduce a copper-magnesium composite coating on the transition layer surface;

[0011] 4) designing an alkaline deplating solution to electrolytically deplating magnesium in a deplating tank to obtain a porous copper coating;

[0012] 5) The porous copper coating material is immersed in angiogenic drugs, and after ultrasonic impregnation loading, drying, light-proof vacuum packaging and irradiation sterilization, the osteogenic-anti-infection dual-function porous copper coating material is obtained.

[0013] Further, in step 1), during the ultrasonic cleaning process, the environmentally friendly degreasing agent is used for cleaning at least once, and deionized water is used for cleaning several times, each cleaning lasting 15-20 minutes; the environmentally friendly degreasing agent includes: sodium carbonate 2-5g / L, sodium metasilicate pentahydrate 3-5g / L, sodium dodecanoate 10-15g / L, nitrilotriacetic acid 3-5ml / L, NP-10 (99%) R2-10g / L, LAB (99%) R5-8g / L, and the rest is deionized water; the ultrasonic power is 50-70w, and the temperature is 50-60°C;

[0014] During the chemical film removal process, an acidic chemical film remover is used to soak the film at room temperature. The acidic chemical film remover includes: 25v / v% phosphoric acid and 2v / v% hydrofluoric acid, and the rest is deionized water.

[0015] Further, in step 2), during the chemical deposition process, the working temperature is 35-40°C, the solution pH is controlled to 10-13, the deposition time is 10-30min, and the copper transition layer thickness is 0.5-1.8 microns; the solution for chemically deposited copper includes: copper sulfate 10-15g / L, sodium hydroxide 8-12g / L, sodium gluconate 5-10g / L, ethylenediaminetetraacetic acid disodium 20-30g / L, potassium sodium tartrate 20-30g / L, and the rest is deionized water.

[0016] Further, in step 3), the Cu 2+ / Mg 2+ The composite electrolyte includes: copper pyrophosphate (anhydrous) 40-50g / L, magnesium sulfate 5-10g / L, potassium pyrophosphate (anhydrous) 200-240g / L, sodium citrate 20-30g / L, disodium ethylenediaminetetraacetic acid 0.5-1.2g / L, sodium hydroxide 15-20g / L, pH value 8-10;

[0017] In the electroplating process, a bidirectional pulse power supply electrochemical deposition mode is adopted, the working temperature is 40-45°C, the forward pulse width is 1-4ms, the forward duty cycle is 10-20%, and the negative current density is 0.3-1.2A / dm 2 , the deposition time is 20-60min, and the anode is oxygen-free electrolytic copper;

[0018] The copper-magnesium composite coating has a thickness of 5-80 microns.

[0019] Further, in step 4), the alkaline electrolytic stripping solution comprises: 20-30 g / L sodium hydroxide, 5-8 g / L disodium ethylenediaminetetraacetate, 5-8 g / L sodium tripolyphosphate, 0.5-1.2 g / L benzotriazole, and the rest is deionized water;

[0020] In the electrolytic stripping process, a bidirectional pulse power supply electrochemical stripping mode is adopted, 304 stainless steel is used as the cathode, the sample workpiece is used as the anode, the forward pulse width is 1-7ms, the forward duty cycle is 20-40%, and the forward current density is 0.8-1.5A / dm 2 The sample stripping temperature is 20-35℃, and the stripping time is 12-30min. After stripping, it is washed with deionized water several times, each time for at least 1 minute. After nitrogen drying, it is placed at 70-80℃ for drying.

[0021] Furthermore, in step 4), the stripping tank is specifically as follows: the tank body is made of polyethylene (PP), the cathode is made of 304 rust-free steel plate, a rocking device is arranged in the tank body for rocking the sample to remove the local accumulation of surrounding ion concentration, the rocking device adopts a 360-degree rotation mode, and the rotation speed is 20-40r / min. During the rocking process, the function of the rocking is that during stripping, the dissolved ions will form a high-concentration concentration gradient around the sample, so that the subsequent stripping process is affected. Therefore, through this rocking device, the concentration gradient around the sample is broken up, which is similar to a stirring operation.

[0022] Furthermore, in step 5), the angiogenic drug is one or more of vascular endothelial growth factor (VEGF), basic fibroblast growth factor (bFGF), deferoxamine, salvianolic acid B, astragaloside, and ginsenoside Deng, and the concentration is 50ng / ml-0.05g / ml;

[0023] The ultrasonic immersion power is 80-100W, the time is 10-15min, and the temperature is 5-8°C;

[0024] The drying temperature is 5-8°C, nitrogen is used, the gas flow rate is 3-6m / s, and the drying time is 5-15min.

[0025] A osteopromoting and anti-infection dual-functional porous metal antibacterial coating material based on dual metal ion electroplating and electrolytic pore-forming technology is obtained by any of the above-mentioned preparation methods.

[0026] Compared with the prior art, the present invention has the following advantages:

[0027] 1) The present invention uses titanium / titanium alloy, copper pyrophosphate, sulfuric acid, angiogenic drugs, etc. as raw materials, and combines chemical deposition, dual metal ion plating, electrolytic stripping, ultrasonic immersion loading, low-temperature nitrogen drying and other combined processes to prepare a osteogenic-anti-infection dual-functional porous metal antibacterial coating material based on dual metal ion plating and electrolytic pore-forming technology. The above raw material selection and process combination are original to the present invention.

[0028] 2) The present invention combines chemical deposition technology to form a copper transition layer on the surface of the titanium substrate, thereby improving the overall bonding strength of the coating. The surface of the titanium substrate is very easy to form an oxide layer, resulting in a low bonding strength of the traditional electrochemical plating on its surface. Therefore, the present invention cleverly uses chemical deposition technology to obtain a copper transition layer on the surface of the titanium substrate, successfully ensuring the bonding strength of the subsequent coating, and the technology is innovative.

[0029] 3) The present invention combines the double metal ion electroplating + electrolytic stripping process to form a copper coating material with a pore structure on the surface of the titanium substrate. + / Mg 2+ The composite electrochemical deposition solution formula, combined with the bimetallic electrochemical deposition process, successfully obtained a copper / magnesium composite bimetallic coating on the surface of the titanium substrate; at the same time, relying on the different redox activities of copper and magnesium elements, the electrolytic stripping process was used to selectively remove the active magnesium element in the composite coating, but the copper element was intact to obtain a copper element coating with a porous structure inside. The construction of the porous copper element coating is based on the synergistic cooperation between the above-mentioned combined processes, while retaining the antibacterial active components, introducing drug loading sites and subsequent inducible cell adhesion functions.

[0030] 4) The pore structure inside the copper coating of the present invention has the function of serving as a bone-promoting drug loading and cell adhesion site. After successfully using the bimetallic electrochemical deposition + electrolytic stripping combined process to introduce a copper single substance coating with a pore structure, the pore structure can be used as an important physical space site. Therefore, the applicant successfully introduced angiogenic drugs into the pore structure by combining the ultrasonic immersion loading + low-temperature nitrogen drying process, and obtained a composite structure of a layer of porous copper single substance coating + two layers of angiogenic drug layers, which solved the technical problems of conventional titanium and the difficulty of secondary introduction of drug loading sites on the coating surface, and provided the possibility for bone implantation / interventional device modification / secondary modification. On the other hand, when the bone implantation / interventional device product containing the above-mentioned composite functional coating is used for the treatment of diseases such as fractures / bone defects, the pore structure on the surface of the copper coating will first serve as a site for inducing cell adhesion. Compared with the flat surface of ordinary titanium, the pore structure is more conducive to the adhesion of cell pseudopodia therein. Cell adhesion is an important prerequisite for subsequent cell proliferation, differentiation, and migration, and can greatly promote bone integration / bone repair process. The above modification strategy of further introducing a pore structure into the copper single-element coating is designed by the present invention in combination with multiple modification requirements of the bone implant device.

[0031] 5) The antibacterial coating material of the present invention has the functions of promoting cell adhesion, promoting blood vessels, promoting osteogenesis, and resisting infection. When it is applied to the process of bone integration / bone repair, cells can first adhere pseudopodia to the surface of the coating through the porous structure of the coating surface, completing the first step of bone repair; at the same time, the internal angiogenic drugs will dissolve and ooze out with the entry of tissue fluid, promoting angiogenesis in the early stage of bone repair, and the new blood vessels can provide nutrients and oxygen for the subsequent new bone formation. And because the microporous structure surrounds and forms a physical barrier, the internal angiogenic drug release cycle is greatly extended, overcoming the toxicity caused by the drug burst release and matching the longer cycle of bone repair; and copper is an effective active ingredient for antibacterial and osteogenesis. In this process, the copper single substance coating will effectively prevent and treat the occurrence of bone infection by slowly dissolving copper ions, achieving the purpose of anti-infection, and the released copper ions can also further promote osteogenesis. It is through the mutual coordination and synergistic enhancement of the above-mentioned cell adhesion, angiogenesis, osteogenesis and anti-infection functions of the antibacterial coating material that fracture / bone repair can be treated efficiently, solving the clinical problems of high incidence of infection and poor bone integration / repair in the process.

[0032] 6) The coating preparation technology in the present invention is a platform technology, which can be modified on the surface of titanium substrates of any shape to meet the modification requirements of various bone implant / interventional device products. The process is convenient and universal, and provides a new strategy for the functional modification of bone implant / interventional device products. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1It is a schematic diagram of the preparation process of the osteogenic and anti-infection dual-function porous metal antibacterial coating material based on the dual metal ion electroplating and electrolytic pore-forming technology of the present invention;

[0034] Figure 2 This is the inhibition zone of the osteogenic and anti-infection dual-functional porous metal antibacterial coating material based on dual metal ion electroplating and electrolytic pore-forming technology in an embodiment of the present invention (A is the base material TC4, and B is Example 1). DETAILED DESCRIPTION

[0035] The present invention is further described below with reference to specific examples and accompanying drawings.

[0036] Comparative Example 1:

[0037] 1) The TC4 sample was ultrasonically cleaned: environmentally friendly degreasing agents (sodium carbonate 5g / L, sodium metasilicate pentahydrate 5g / L, sodium dodecanoate 10g / L, nitrilotriacetic acid 5ml / L, NP-10 (99%) R 10g / L, LAB (99%) R 8g / L, the rest was deionized water, temperature 55°C) were used in sequence, the ultrasonic power was 60W, each cleaning time was 20min, cleaning once, deionized water was washed three times, and after cleaning, the sample was subjected to acidic chemical defilming (25v / v% phosphoric acid, hydrofluoric acid 2v / v%, the rest was deionized water); chemical defilming was carried out by soaking at room temperature for 70s, and the next process was carried out after washing with deionized water three times.

[0038] 2) A copper transition layer was formed on the surface of the substrate using a chemical deposition process (working solution temperature 35°C, solution pH = 12.5, deposition time 900s), wherein the plating solution formula was: 15g / L copper sulfate, 12g / L sodium hydroxide, 10g / L sodium gluconate, 20g / L disodium ethylenediaminetetraacetic acid, 20g / L potassium sodium tartrate, and the rest was deionized water, and the resulting copper transition layer had a thickness of 1.1 microns.

[0039] 3) Combined with dual metal ion plating process (pH value 8-10, anode is oxygen-free electrolytic copper, working fluid temperature 45°C, positive pulse width 4ms, positive duty cycle 15%, negative current density 0.5A / dm 2 , deposition time is 25min) a copper-magnesium composite coating is further introduced on the transition layer surface, wherein Cu 2+ / Mg 2+ The composite electrolyte formula is: copper pyrophosphate (anhydrous) 45g / L, magnesium sulfate 8g / L, potassium pyrophosphate (anhydrous) 200g / L, sodium citrate 25g / L, disodium ethylenediaminetetraacetic acid 0.8g / L, sodium hydroxide 15g / L. The obtained copper-magnesium composite coating has a thickness of about 18.5 microns.

[0040] 4) Place the composite coating sample in a stripping tank (the tank body is made of PP material, the cathode is 304 stainless steel plate, and a swing device is designed in the electrolytic tank. The swing device adopts a 360-degree rotation mode and a rotation speed of 30r / min) to remove the magnesium element in the composite coating and obtain a porous copper coating. The stripping solution formula is: 25g / L sodium hydroxide, 7g / L disodium ethylenediaminetetraacetic acid, 7g / L sodium tripolyphosphate, and 0.8g / L benzotriazole. A bidirectional pulse power supply electrochemical stripping mode is used, 304 stainless steel is used as the cathode, the sample workpiece is used as the anode, the forward pulse width is 2ms, the forward duty cycle is 30%, and the forward current density is 1.3A / dm 2 The temperature of the deplating solution is 35°C, and the deplating time is 30 minutes. After the deplating is completed, it is washed with deionized water for 3 times, each time for 10 minutes, and after nitrogen drying, it is placed in a vacuum oven at 80°C. After light-proof vacuum packaging and irradiation sterilization, the metal coating material is obtained.

[0041] The extract of the coating material was prepared and co-cultured with mesenchymal stem cells for 7 days. The CCK-8 test results showed that the cell survival rate was about 88.4%. The coating bonding strength was about 32.4 MPa using a universal testing machine. The antibacterial zone area of ​​the coating was about 2.14 cm 2 ; It was implanted into a rat intramedullary infection model. The bone infection disappeared after 4 weeks, and the bone integration effect of the sample surface was average.

[0042] Embodiment 1:

[0043] 1) The TC4 sample was ultrasonically cleaned: environmentally friendly degreasing agents (sodium carbonate 5g / L, sodium metasilicate pentahydrate 5g / L, sodium dodecanoate 10g / L, nitrilotriacetic acid 5ml / L, NP-10 (99%) R 10g / L, LAB (99%) R 8g / L, the rest was deionized water, temperature 55°C) were used in sequence, the ultrasonic power was 60W, each cleaning time was 20min, cleaning once, deionized water was washed three times, and after cleaning, the sample was subjected to acidic chemical defilming (25v / v% phosphoric acid, hydrofluoric acid 2v / v%, the rest was deionized water); chemical defilming was carried out by soaking at room temperature for 70s, and the next process was carried out after washing with deionized water three times.

[0044] 2) A copper transition layer was formed on the surface of the substrate using a chemical deposition process (working solution temperature 35°C, solution pH = 12.5, deposition time 900s), wherein the plating solution formula was: 15g / L copper sulfate, 12g / L sodium hydroxide, 10g / L sodium gluconate, 20g / L disodium ethylenediaminetetraacetic acid, 20g / L potassium sodium tartrate, and the rest was deionized water, and the resulting copper transition layer had a thickness of 1.1 microns.

[0045] 3) Combined with dual metal ion plating process (pH value 8-10, anode is oxygen-free electrolytic copper, working fluid temperature 45°C, positive pulse width 4ms, positive duty cycle 15%, negative current density 0.5A / dm 2 , deposition time is 25min) a copper-magnesium composite coating is further introduced on the transition layer surface, wherein Cu 2+ / Mg 2+ The composite electrolyte formula is: copper pyrophosphate (anhydrous) 45g / L, magnesium sulfate 8g / L, potassium pyrophosphate (anhydrous) 200g / L, sodium citrate 25g / L, disodium ethylenediaminetetraacetic acid 0.8g / L, sodium hydroxide 15g / L. The obtained copper-magnesium composite coating has a thickness of about 18.5 microns.

[0046] 4) Place the composite coating sample in a stripping tank to remove the magnesium element in the composite coating and obtain a porous copper coating (the tank body is made of PP material, the cathode is made of 304 stainless steel plate, and a swing device is designed in the electrolytic tank. The swing device adopts a 360-degree rotation mode with a rotation speed of 30r / min; the working liquid formula is: sodium hydroxide 25g / L, ethylenediaminetetraacetic acid disodium 7g / L, sodium tripolyphosphate 7g / L, and benzotriazole 0.8g / L). A bidirectional pulse power supply electrochemical stripping mode is used, 304 stainless steel is used as the cathode, the sample workpiece is used as the anode, the forward pulse width is 2ms, the forward duty cycle is 30%, and the forward current density is 1.3A / dm 2 The temperature of the deplating solution was 35°C and the deplating time was 30 min. After the deplating was completed, it was washed with deionized water for 3 times, each time for 1 min. After nitrogen drying, it was placed in an oven at 80°C.

[0047] 5) The sample was immersed in VEGF (concentration of 0.05 g / ml), ultrasonically immersed (ultrasonic immersion power of 80 W, time of 15 min, temperature of 8°C), low-temperature nitrogen dried (temperature of 5°C, gas flow rate of 3 m / s, drying time of 15 min), and then light-proof vacuum packaging and irradiation sterilization to obtain the osteogenic-anti-infection dual-functional porous metal antibacterial coating material.

[0048] Compared with Comparative Example 1, this embodiment introduces vascular endothelial growth factor into the copper coating by electroplating / deplating magnesium. The extract of the above coating material was prepared and co-cultured with mesenchymal stem cells for 7 days. The CCK-8 test results showed that the cell survival rate was about 90.6%; the coating bonding strength was about 31.3MPa using a universal testing machine; the coating inhibition zone area was about 2.01cm 2 ,like Figure 2 As shown in B, it was implanted into a rat intramedullary infection model. After 4 weeks, the bone infection disappeared and the bone integration effect on the sample surface was excellent.

[0049] Embodiment 2:

[0050] 1) The TC4 sample was ultrasonically cleaned: environmentally friendly degreasing agents (sodium carbonate 5g / L, sodium metasilicate pentahydrate 5g / L, sodium dodecanoate 10g / L, nitrilotriacetic acid 5ml / L, NP-10 (99%) R 10g / L, LAB (99%) R 8g / L, the rest was deionized water, temperature 55°C) were used in sequence, the ultrasonic power was 60W, each cleaning time was 20min, cleaning once, deionized water was washed three times, and after cleaning, the sample was subjected to acidic chemical defilming (25v / v% phosphoric acid, hydrofluoric acid 2v / v%, the rest was deionized water); chemical defilming was carried out by soaking at room temperature for 70s, and the next process was carried out after washing with deionized water three times.

[0051] 3) Combined with dual metal ion plating process (pH value 8-10, anode is oxygen-free electrolytic copper, working fluid temperature 45°C, positive pulse width 4ms, positive duty cycle 15%, negative current density 0.5A / dm 2 , deposition time is 25min) a copper-magnesium composite coating is further introduced on the sample surface, wherein Cu 2+ / Mg 2+ The composite electrolyte formula is: copper pyrophosphate (anhydrous) 45g / L, magnesium sulfate 8g / L, potassium pyrophosphate (anhydrous) 200g / L, sodium citrate 25g / L, disodium ethylenediaminetetraacetic acid 0.8g / L, sodium hydroxide 15g / L. The obtained copper-magnesium composite coating has a thickness of about 18.5 microns.

[0052] 4) Place the composite coating sample in a stripping tank to remove the magnesium element in the composite coating and obtain a porous copper coating (the tank body is made of PP material, the cathode is made of 304 stainless steel plate, and a swing device is designed in the electrolytic tank. The swing device adopts a 360-degree rotation mode with a rotation speed of 30r / min; the working liquid formula is: sodium hydroxide 25g / L, ethylenediaminetetraacetic acid disodium 7g / L, sodium tripolyphosphate 7g / L, and benzotriazole 0.8g / L). A bidirectional pulse power supply electrochemical stripping mode is used, 304 stainless steel is used as the cathode, the sample workpiece is used as the anode, the forward pulse width is 2ms, the forward duty cycle is 30%, and the forward current density is 1.3A / dm 2 The temperature of the deplating solution was 35°C and the deplating time was 30 min. After the deplating was completed, it was washed with deionized water for 3 times, each time for 1 min. After nitrogen drying, it was placed in an oven at 80°C.

[0053] 5) The sample was immersed in VEGF (concentration of 0.05 g / ml), ultrasonically immersed (ultrasonic immersion power of 80 W, time of 15 min, temperature of 8°C), low-temperature nitrogen dried (temperature of 5°C, gas flow rate of 3 m / s, drying time of 15 min), and then light-proof vacuum packaging and irradiation sterilization to obtain a porous metal coating material.

[0054] Compared with Example 1, this example reduces the introduction of the transition layer. The extract of the coating material was prepared and co-cultured with mesenchymal stem cells for 7 days. The CCK-8 test results showed that the cell survival rate was about 84.5%; the coating bonding strength was about 20.8MPa using a universal testing machine; the coating inhibition zone area was about 2.92cm 2 ; It was implanted into a rat intramedullary infection model. The coating partially fell off during the operation, and the bone infection disappeared after 4 weeks. The sample surface had excellent bone integration effect.

Claims

1. A method for preparing a osteogenic and anti-infection dual-function porous metal antibacterial coating material based on dual metal ion electroplating and electrolytic pore-forming technology, characterized in that: The following steps are involved: 1) Using an environmentally friendly degreasing agent and deionized water under ultrasonic cleaning conditions to remove impurities on the surface of the titanium substrate and perform chemical film removal; 2) forming a copper transition layer on the surface of the titanium substrate using a chemical deposition process; 3) Design Cu 2+ / Mg 2+ The composite electrolyte formula combines the dual metal ion electroplating process to introduce a copper-magnesium composite coating on the transition layer surface; 4) designing an alkaline deplating solution to electrolytically deplating magnesium in a deplating tank to obtain a porous copper coating; 5) The porous copper coating material is immersed in angiogenic drugs, and after ultrasonic impregnation loading, drying, light-proof vacuum packaging and irradiation sterilization, the osteogenic-anti-infection dual-function porous copper coating material is obtained.

2. According to claim 1, a method for preparing a osteogenic and anti-infection dual-function porous metal antibacterial coating material based on dual metal ion electroplating and electrolytic pore-forming technology, characterized in that: In step 1), during the ultrasonic cleaning process, the environmentally friendly degreasing agent is used for cleaning at least once, and the deionized water is used for cleaning several times, each cleaning time is 15-20 minutes; the environmentally friendly degreasing agent includes: sodium carbonate 2-5g / L, sodium metasilicate pentahydrate 3-5g / L, sodium dodecanoate 10-15g / L, nitrilotriacetic acid 3-5ml / L, NP-10 (99%) R2-10g / L, LAB (99%) R5-8g / L, and the rest is deionized water; the ultrasonic power is 50-70w, and the temperature is 50-60°C; In the chemical film removal process, an acidic chemical film remover is used to soak the film at room temperature. The acidic chemical film remover includes: 25v / v% phosphoric acid and 2v / v% hydrofluoric acid, and the rest is deionized water.

3. The method for preparing a osteogenic and anti-infection dual-function porous metal antibacterial coating material based on dual metal ion electroplating and electrolytic pore-forming technology according to claim 1, characterized in that: In step 2), during the chemical deposition process, the working temperature is 35-40°C, the solution pH is controlled to 10-13, the deposition time is 10-30min, and the copper transition layer thickness is 0.5-1.8 microns; the solution for chemically deposited copper includes: copper sulfate 10-15g / L, sodium hydroxide 8-12g / L, sodium gluconate 5-10g / L, disodium ethylenediaminetetraacetate 20-30g / L, potassium sodium tartrate 20-30g / L, and the rest is deionized water.

4. The method for preparing a osteogenic and anti-infection dual-function porous metal antibacterial coating material based on dual metal ion electroplating and electrolytic pore-forming technology according to claim 1, characterized in that: In step 3), the Cu 2+ / Mg 2+ The composite electrolyte includes: copper pyrophosphate (anhydrous) 40-50g / L, magnesium sulfate 5-10g / L, potassium pyrophosphate (anhydrous) 200-240g / L, sodium citrate 20-30g / L, disodium ethylenediaminetetraacetic acid 0.5-1.2g / L, sodium hydroxide 15-20g / L, pH value 8-10; In the electroplating process, a bidirectional pulse power supply electrochemical deposition mode is adopted, the working temperature is 40-45°C, the forward pulse width is 1-4ms, the forward duty cycle is 10-20%, and the negative current density is 0.3-1.2A / dm 2 , the deposition time is 20-60min, and the anode is oxygen-free electrolytic copper; The copper-magnesium composite coating has a thickness of 5-80 microns.

5. The method for preparing a osteogenic and anti-infection dual-functional porous metal antibacterial coating material based on dual metal ion electroplating and electrolytic pore-forming technology according to claim 1, characterized in that: In step 4), the alkaline electrolytic stripping solution includes: 20-30 g / L sodium hydroxide, 5-8 g / L disodium ethylenediaminetetraacetate, 5-8 g / L sodium tripolyphosphate, 0.5-1.2 g / L benzotriazole, and the rest is deionized water; In the electrolytic stripping process, a bidirectional pulse power supply electrochemical stripping mode is adopted, 304 stainless steel is used as the cathode, the sample workpiece is used as the anode, the forward pulse width is 1-7ms, the forward duty cycle is 20-40%, and the forward current density is 0.8-1.5A / dm 2 The sample stripping temperature is 20-35℃, and the stripping time is 12-30min. After stripping, it is washed with deionized water several times, each time for at least 1 minute. After nitrogen drying, it is placed at 70-80℃ for drying.

6. The method for preparing a osteogenic and anti-infection dual-function porous metal antibacterial coating material based on dual metal ion electroplating and electrolytic pore-forming technology according to claim 1, characterized in that: In step 4), the stripping tank is specifically as follows: the tank body is made of polyethylene (PP), the cathode is made of 304 rust-free steel plate, and a rocking device is arranged in the tank body for rocking the sample to remove the local accumulation of surrounding ion concentration. The rocking device adopts a 360-degree rotation mode with a rotation speed of 20-40r / min.

7. The method for preparing a osteogenic and anti-infection dual-function porous metal antibacterial coating material based on dual metal ion electroplating and electrolytic pore-forming technology according to claim 1, characterized in that: In step 5), the angiogenic drug is one or more of vascular endothelial growth factor (VEGF), basic fibroblast growth factor (bFGF), deferoxamine, salvianolic acid B, astragaloside, and ginsenoside A, with a concentration of 50 ng / ml-0.05 g / ml; The ultrasonic immersion power is 80-100W, the time is 10-15min, and the temperature is 5-8°C; The drying temperature is 5-8°C, nitrogen is used, the gas flow rate is 3-6m / s, and the drying time is 5-15min.

8. A osteogenic and anti-infection dual-function porous metal antibacterial coating material based on dual metal ion electroplating and electrolytic pore-forming technology, characterized in that: The method is adopted as described in any one of claims 1 to 7.

Citation Information

Patent Citations

  • Production process for preparing copper-magnesium alloy by virtue of molten salt electrolysis method

    CN104388986A

  • Preparing method for magnesium copper alloy

    CN107059060A